중학생의 흡연수용태도를 결정하는 요인 - 지인순 (연세대학교 보건대학원, 1989)
흡연이 인간의 신체 및 정신에 미치는 영향에 관하여 지금까지 많은 연구가 진행되어 왔으나 대부분의 흡연자들이 담배의 해독이나 전문가의 경고에도 불구하고 계속 흡연하고 있으며 최근에는 청소년층 흡연인구의 증가와 연소화의 경향을 보이고 있다. 그러나 왜 흡연을 하는 지에 대한 이유는 아직 확실히 밝혀지지 않고 있으며 더욱이 성장기에 있는 청소년기의 흡연은 신체 및 정신건강에 미치는 영향이 매우 심각하다. 이에 본 연구는 청소년의 흡연시도를 중요하게 작용할 중학생의 흡연수용태도를 결정하는 요인을 파악하고자 시도하였다. 본 연구는 흡연과 관련있으리라 생각되는 여러요인 중 문헌고찰 결과 중요한 의미가 있는 가정환경, 자아개념, 건강통제위성격 요인을 선정하여 중학생의 흡연수용태도와의 관련성을 검증하기 위하여 서울 시내의 한 중학교에서 임의표집한 506명(남학생 248명, 여학생258명)을 연구대상으로 하였으며, 조사방법은 김기정이 제작한 가정환경조사와 자아개념검사, K·A Wallston & B·S Wallston이 개발한 다차원건강통제위성격척도, 연구자가 제작한 흡연에 대한 태도측정도구를 이용하여 질문지법에 의한 자료수집을 1989년 5월 1 2일부터 1989년 5월 13일까지 하였다. 자료분석은 대상자의 가정환경, 자아개념, 건강통제위성격, 흡연에 대한 태도, 흡연경험 여부를 확인하기 위하여 실수와 백분율을 산출하여 X^^2 검정을 통해 남·여학생을 비교하였고, 흡연수용태도, 흡연경험과 가정환경, 자아개념, 건강통제위성격과의 관련성을 알아보기 위하여 X^^2검정을 하였으며 X^^2검정 결과 의미있는 요인에 문헌고찰 결과 중요하다고 인정되는 요인을 첨가하여 대수선형검정(loglinear-test)하였다. 본 연구의 결과는 다음과 같다. 1. 조사 대상자 506명(남학생 248명, 여학생 258명)중 흡연수용태도를 나타낸 학생은 남학생 125명(50.4%), 여학생 116명(45%)이었고 흡연경험이 있는 학생은 남학생 61명(24.6%), 여학생 17(6.6%)이었다. 2. 흡연에 대한 태도는 남·여학생 모두에서 비교적 흡연에 대하여 거부적 태도를 나타냈는데, 여성의 흡연에 대하여 가장 거부적 태도를 보였으며 장래 배우자의 흡연에 대하여는 남학생이 여학생보다 거부적 태도가 강했고 남성의 흡연과 영상매체에서의 흡연장면에 대하여는 여학생이 남학생보다 더 거부적이었다. 공공장소에서의 흡연 구역 설정과 금연운동의 필요성에 대하여 남·여학생 모두에서 긍정적인 태도를 나타냈으며 여학생이 남학생보다 더 긍정적인 태도를 나타냈다. 3. 흡연수용태도와 가정환경, 자아개념, 건강통제위성격과의 관계를 분석한 결과 남학생의 경우 아버지의 흡연, 형제의 흡연, 부모의 거부적 양육태도, 성격적 자아개념이, 여학생의 경우는 부모의 거부적 양육태도가 관련성 있는 요인으로 나타났다. 4. 흡연경험과 가정환경, 자아개념, 건강통제위성격, 흡연에 대한 태도와의 관계를 분석한 결과 남학생의 경우 아버지의 교육수준, 아버지의 흡연, 형제의 흡연, 한달 용돈액수, 흡연에 대한 수용태도가, 여학생의 경우는 타인의존성향, 한달 용돈액수가 관련성있는 요인으로 나타났다. 5. 흡연수용태도 요인분석 결과 남학생의 경우 부모의 거부적 양육태도, 아버지의 흡연이, 여학생의 경우는 부모의 거부적 양육태도, 우연성향, 부정적 자아개념, 아버지의 흡연이 관련성 있는 요인으로 나타났다. 6. 흡연경험 요인분석 결과 남학생의 경우 형제의 흡연, 부모의 거부적 양육태도, 한달 용돈액수, 우연성향이, 여학생의 경우는 부모의 거부적 양육태도, 부정적 자아개념이 관련성있는 요인으로 나타났다. 이상의 결과를 통하여 가족원의 흡연, 한달 용돈액수, 부모의 거부적 양육태도와 부정적 자아개념, 우연성향이 관련있는 요인으로 나타나 이들 요인이 중학생의 흡연수용태도를 결정하는데 중요한 역할을 하므로 가정과 사회의 건정한 환경조성이 요구되며 가정과 학교에서 긍정적 사고 육성을 위한 특별한 지도가 필요하다고 생각한다. Many studies have been conducted about the influence of smoking on the body and mind of a human, Most smokers smoke continuously in spite of the harm of smoking and warnings by specialists. There is recently an increase in adolescent smokers continue to smoke and smoke at an increasingly early age has not come to light yet. Thus this study make an attempt to understand factors affecting the smoking attitudes of middle school students. This study selected the factors of home environment, self-concept and health locus control and tested their relationship to the smoking attitude of middle school students. To this purpose, 506 students (248 boys, 258 girls) in a middle school located in Seoul were sampled. The study method was by questionnaire using the home environment search and self-concept test made by kim, the multidimensional health locus of control scale developed by Wallston & Wallston and the attitude measurement tool for smoking developed by the researcher. The period for data collection was from the 12th to 13th of May, 1989. The collected data were analyzed using descriptive statistics, X^^2-test and a loginear-test. The results of the study are as follows: 1. Among 506 students (248 boys, 258 girls), 125 boys(50.4%) had attitude of accepting smoking, and 116 girls(45%) did. 61 boys(24.6%) and 17 girls(6.6%) were experienced in smoking. 2. Boys and girl showed relatively negative attitude about smoking and showed most negative attitude about woman's smoking. Boys showed more negative attitude about smoking of future spouse than girls and girls showed more negative attitude about smoking of man, smoking scene of picture media than boys, Boys and girls showed positive attitude about fixing a zone of "no smoking" and the necessity of no smoking movement. Especially girls were more positive. 3. As the result of analyzing the relation between smoking attitude and home environment, self-concept and health locus of control, the boys related their smoking attitude to their father's and brother's smoking, the negative rearing attitude of their parents, and a characteristic self-concept. The girls related their smoking attitude to the negative rearing attitude of their parents. 4. As the result of analyzing the relation between smoking attitude and home environment, self-concept, health locus of control and attitude toword smoking, boys related their smoking to the education level of their father, their father's and brother's smoking, anount of monthly spending money and the acceptance attitude of smoking. The girls related their smoking to the health locus of control variable of powerful others and amount of monthly spending money. 5. As the result of analyzing the factor of smoking attitude, boys related their smoking attitude to the negative rearing attitude of their parents and the smoking of their father. The girls related their smoking attitude to the negative rearing attitude of their parents, the health locus of control variable of chance, a negative self-concept and the smoking of their father. 6. As the result of analyzing the factor of smoking experience, boys related their smoking to their brother's smoking, the negative rearing attitude of their parents, amount on monthly spending money and the health locus of control variable of chance. The girls related their smoking to the negative rearing attitude of their parents and a negative self concept. To summarize the above results, the middle school students were affected by smoking of their family members, amount of monthly spending money, the negative rearing attitude of their parents, a negative self-concept and the health locus of control variable of chance. Thus, these factors play an important role in determining the smoking attitude of middle school students. Consequently, it is demanded to make the healthy environment of home and society. And health education is needed to promote a change in attitude, self-concept, and health locus of control character.
보건간호학과/석사